"We Are All Humans and Deserve a Decent Way to Go": Examining Professional's Experiences With Providing End-of-Life Care in Correctional Institutions. (June 2022) - Steely Smith, Mollee; Cooley, Brooke; Bensel, Tusty ten
The aging prison population has increased dramatically over the past two decades. As this population increases, correctional institutions are faced with health care challenges. Specifically, providing adequate end-of-life (EOL) care for terminally ill inmates has been a concern. Despite issues relating to providing EOL care, little is known about medical and correctional staff's attitudes toward the implementation of EOL care. The purpose of this study was to understand the challenges faced by correctional and medical professionals, focusing on job satisfaction, obstacles, and emotional effects of providing EOL care in correctional institutions. Our data included 17 semistructured, face-to-face interviews with medical and correctional staff assigned to the EOL care unit in a southern state. Although the entire sample stated overall satisfaction with their job, participants noted several challenges and stressors, which included the lack of resources and difficulties in balancing care. Participants agreed that it was emotionally stressful to maintain appropriate relationships with the inmates, deal with patient manipulation, and be surrounded by dying and death. Implications are discussed relative to the needs and experiences of service providers and how to more effectively treat EOL inmate patients.